Identification and Comparison of Phytoconstituents of Essential Oil and Methanolic Extracts of Leaves and Rhizomes of Elettariopsis curtisii Grown in Malaysia via GCMS Analysis - Najlaa, Engku Nurul; Sultan, Sadia; Ashraf, Kamran (Indian Journal of Pharmaceutical Education and Research, 2025)
Introduction: Elettariopsis curtisii (Zingiberaceae) is a high-value medicinal plant that has been used by the locals in Southeast Asia mainly to treat bloating and for postnatal care purposes. It contains many valuable phytoconstituents, including various essential oils that might be used in the treatment of various diseases. All previous studies were mainly carried out on the essential oil of rhizomes, and no or very limited information is available on other parts of the plant and methanolic extracts. Thus, this current study was conducted to identify, characterize, and compare the phytoconstituents of rhizome and leaf essential oils and methanolic extracts of E. curtisii grown in Malaysia via GCMS analysis. Materials and Methods: The plant samples were collected from a nursery in Kuala Krai, Kelantan, Malaysia. The extraction of essential oils from rhizomes and leaves was carried out via hydrodistillation and simple cold maceration method using methanol as solvent, respectively. Later on, all samples were analysed via GCMS analysis, and phytoconstituent identification was done based on the comparison in the NIST08 library. Results: A number of compounds were identified by GCMS analysis in rhizome essential oil, leaf essential oil, methanol rhizome extract and methanol leaf extract of E. curtisii. The most abundant phytoconstituent reported in rhizome essential oil was (E)-2-Decenal. The compound (E)-2-octenal, is found to be present in highest concentration in leaf essential oil, methanol rhizome extract, and methanol leaf extract, with peak areas of 41.11%, 40.68%, and 54.14%, respectively. Literature shows the beneficial antimicrobial and antioxidant nature of these identified compounds. Conclusion: This study might provide valuable information about the phytoconstituents found in this plant and could help the researcher in the isolation of antimicrobial compounds. We also recommend performing LCMS analysis on the extracts prior to isolating the desired compounds.
Keywords: Elettariopsis curtisii; Essential oil; Methanolic extract; GCMS analysis